Economic performance of smallholder irrigation schemes: A case study in Zanyokwe, Eastern Cape, South Africa - Perret, S. (Sylvain) (University of Pretoria, 2013)
Dissertation (M Inst Agrar (Agricultural Economics))--University of Pretoria, 2007.